2018
DOI: 10.1159/000493816
|View full text |Cite
|
Sign up to set email alerts
|

Fangjifuling Ameliorates Lipopolysaccharide-Induced Renal Injury via Inhibition of Inflammatory and Apoptotic Response in Mice

Abstract: Background/Aims: Acute kidney injury (AKI) is a frequent and serious complication of sepsis; however, there is no effective treatment for it. FangJiFuling (FF) decoction is widely used to treat acute glomerulonephritis and nephritic syndrome in the clinical setting. Methods: On the basis of its anti-inflammatory properties, the renoprotective effect of FF on a mouse model of lipopolysaccharide (LPS)-induced AKI was investigated. Major compounds were identified in FF with high-performance liquid chromatography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Previous studies have shown that LPS could directly lead to renal tubular cell injury and AKI by binding to TLR4 (6,2729). Consistent with previous studies (6,911), the present study found that LPS induced renal tubular epithelial cell apoptosis in vitro and in vivo . However, the mechanisms of LPS-induced tubular epithelial cell apoptosis are not completely understood.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that LPS could directly lead to renal tubular cell injury and AKI by binding to TLR4 (6,2729). Consistent with previous studies (6,911), the present study found that LPS induced renal tubular epithelial cell apoptosis in vitro and in vivo . However, the mechanisms of LPS-induced tubular epithelial cell apoptosis are not completely understood.…”
Section: Discussionsupporting
confidence: 93%
“…LPS not only triggers a large number of inflammatory cytokines, but can also directly induce renal tubular epithelial cell injury through the activation of Toll-like receptor 4 (TLR4). Tubular epithelial cell apoptosis is one of the characteristic changes that occurs in LPS-induced AKI (1,4,7,8), and accumulating evidence has demonstrated that tubular epithelial cell apoptosis has an important role in LPS-induced AKI (6,911). Inhibiting tubular epithelial cell apoptosis could be an effective strategy to prevent or treat LPS-induced AKI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several substances have been reported to exert therapeutic effects in a cecal ligation and puncture (CLP) mouse model primarily through inhibiting tubular cell apoptosis [27,28]. Tubular cell apoptosis was also observed in LPS-injected rodents [29,30], where the administration of a pan-caspase inhibitor was shown to ameliorate LPS-induced AKI [31]. In our study, LPS treatment increased the amounts of lipid peroxidation products and reversed a reduction in GSH/GSSG ratio in the kidneys.…”
Section: Discussionsupporting
confidence: 54%
“…erefore, the inhibition of inflammation and oxidative stress may serve as a good strategy for the treatment of CKD. Su et al reported the renal protective effect of Fangjifuling against LPS-induced inflammatory and apoptotic responses in vitro and in vivo [29]. Similar protective effects were reported for berberine against chronic renal failure mediated via tumor necrosis factor receptor associated factor 5-(TRAF5-) induced activation of the NF-κB signaling pathway in mouse podocytes [30].…”
Section: Discussionmentioning
confidence: 73%